Solids Go Bio: Inorganic Nanoparticles as Enzyme Mimics - Ragg, Ruben; Tahir, Muhammad N.; Tremel, Wolfgang (European journal of inorganic chemistry, 2016)
A longstanding goal of biomimetic chemistry is the design and synthesis of functional enzyme mimics. The past three decades have seen a wide variety of materials, including metal complexes, polymers and other biomolecules, that mimic the structures and functions of naturally occurring enzymes. Among these, inorganic nanoparticles offer huge potential, because they are more stable than their natural counterparts, while having large surface areas and sizes comparable to those of natural enzymes. Therefore, a considerable number of “artificial enzymes” derived from inorganic nanomaterials have been reported. This microreview highlights the recent progress in the field of enzymatically active inorganic nanomaterials, including mimics of peroxidases, haloperoxidases, superoxide dismutases and sulfite oxidases, along with selected biotechnological applications and their future prospects. This microreview highlights the recent progress in the field of nanoparticles possessing enzyme‐like activities, including peroxidase, haloperoxidase, superoxide dismutase and sulfite oxidase mimics. Inorganic nanoparticles are more stable and cost‐efficient in synthesis than their natural counterparts, while exhibiting equally high enzymatic activities.